Efficiency of partial 16S rRNA gene sequencing as molecular marker for phylogenetic study of cyanobacteria, with emphasis on some complex taxa - Shariatmadari, Zeinab; Moharrek, Farideh; Riahi, Hossein; Heidari, Fatemeh; Aslan, Elaheh (Acta Biologica Szegediensis, 2017)
At present, the analysis of 16S rRNA gene sequences is the most commonly used molecular marker for phylogenetic studies of cyanobacteria. However, in many studies partial sequences is used. To evaluate the performance of this molecular marker, phylogenetic relationship of several taxa from this phylum, especially some intermixed taxa, was studied. We analyzed a data set consisting of three categories of cyanobacterial strains, traditionally classified in three orders, by morphological and phylogenetic analyses. The phylogenetic analyses were performed with an emphasis on partial 16S rRNA gene sequences (600 bp) and the phylogenetic relationships were assessed using Maximum Parsimony, Maximum Likelihood and Bayesian Inference. In morphometric study, numerical taxonomy was performed on several morphospecies, and cluster analysis was performed using SPSS software. Based on the findings of this study, unlike the morphological analysis which was useful in several taxonomic ranks, this molecular marker is recommended for use only in high taxonomic levels such as order and family, because, contrary to our expectations, using partial 16S rRNA gene sequencing in the lower taxonomic levels, even in the genus level, was not necessarily successful. Inefficiency of this molecular marker in taxonomy of some genera, especially intermixed taxa, was another finding of the present study, which represents the genetic similarity of these taxa.